Horseshoe Crab Aquaculture as a Sustainable Endotoxin Testing Source - Tinker-Kulberg, Rachel; Dellinger, Kristen; Brady, Terry E.; Robertson, Lee; Levy, Jerrold H.; Abood, Sarah K.; LaDuca, Frank M.; Kepley, Christopher L.; Dellinger, Anthony L. (Frontiers in Marine Science, 2020)
Horseshoe crab (HSC) hemolymph is the source of Limulus amebocyte lysate (LAL), a critical component in sterility testing that ensures drug and medical device safety for millions of patients every year. Wild HSC populations have been declining as a result of its use as whelk and eel bait, environmental changes, and its capture and bleeding for hemolymph by the biomedical industry, thus posing significant risks to species viability and the LAL raw material supply chain. We designed a controlled aquaculture habitat to husband HSCs and evaluated the effects of captivity on health markers (e.g., amebocyte density, hemocyanin levels, and LAL activity). We found HSC aquaculture to be practicable, with routine hemolymph harvesting resulting in high LAL quality, while safeguarding animal well-being with 100% HSC survival. Further, low-impact hemolymph harvesting via an indwelling catheter revealed rapid amebocyte rebound kinetics after consecutive 10% hemolymph extractions. Sustainable supplies of LAL could also be adapted to address daunting trends in septicemia and antimicrobial resistance. LAL is uniquely sensitive and specific for gram-negative bacteria, which represent 70–80% of pathogens that typically lead to sepsis. However, erratic results associated with interfering substances plagued efforts to adapt LAL for clinical use in the past. We report the development of a new LAL-based assay that can detect gram-negative bacteria and endotoxins in human blood without interference using aquaculture-derived LAL. Based on this research, sustainable LAL production from aquaculture could potentially satisfy industry needs with a fraction of one year’s current capture via year-round harvesting from a finite cohort of HSCs and expand raw materials supplies for potential future clinical applications.